The Effect of Price Earning Ratio, Firm Size, and Corporate Social Responsibility on Firm Value (Empirical Study on Pharmaceutical Sub-Sector Companies Listed on The Indonesia Stock Exchange 2016 – 2020 Period) - Trevhy Firdha Wahyuni Marc; D P Suciwati; I Gede Made Karma (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
Investors can use the firm value to see the company's performance in the past and predict the company's performance in the future. There are many factors that can affect the firm value in the future, including the company's ability to generate profits, the scale of the company, and the company's responsibility to stakeholders. However, there is a difference between expectations and the phenomena that occur in the field regarding these factors. The purpose of this research was to determine the effect of Price Earning Ratio, Firm Size, and Corporate Social Responsibility either partially or simultaneously on the value of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The type of data used in this research is quantitative data, namely the annual financial statements of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. The sample selection in this research was based on purposive sampling method, so that the sample used in this research amounted to 45 companies for 5 years. The data analysis technique used is multiple linear regression analysis. The results showed that partially Price Earning Ratio had a significant positive effect on firm value, while Firm Size and Corporate Social Responsibility had no significant effect on firm value. Simultaneously, Price Earning Ratio, Firm Size, and Corporate Social Responsibility have a significant effect on the value of pharmaceutical companies listed on the Indonesia Stock Exchange by 19.4%.